Anxiety Sensitivity and Reactivity to Asthma-Like Sensations Among Young Adults With Asthma. (January 2016) - McLeish, Alison C.; Luberto, Christina M.; O'Bryan, Emily M.
Anxiety sensitivity, particularly the physical concerns domain, is associated with more problematic asthma symptoms and greater functional limitations. It has been theorized that anxiety sensitivity fosters greater reactivity to asthma-related physical sensations; however, this theory has yet to be empirically tested. Thus, the present investigation sought to examine the role of anxiety sensitivity–physical concerns in terms of affective and physical reactivity to asthma-like symptoms. Participants were 101 undergraduates with asthma (76.2% female, M age = 19.69 years, SD = 3.77 years, range = 18-49 years) who completed self-report measures and a straw-breathing task. Results indicated that after controlling for the effects of gender, asthma control (i.e., how well one's asthma symptoms are managed or controlled), and negative affectivity, greater levels of anxiety sensitivity–physical concerns significantly predicted greater anxiety (4.7% unique variance) and asthma symptoms (6.9% unique variance) and lower levels of lung function (4.4% unique variance) after the straw-breathing task. These findings suggest that individuals with asthma who are fearful of physiological arousal are a particularly "at-risk" population for poor asthma outcomes because of this greater reactivity and could benefit from interventions targeting anxiety sensitivity.